Uganda : A Review of the World Bank Jobs Portfolio - Parikh, Vismay; Clay, Timothy (World Bank, Washington, DC, 2020)
In the past decade, Uganda has made significant progress in reducing poverty and sustaining high economic growth. However, Uganda still faces considerable challenges that include poor infrastructure, weak public service delivery, low levels of human capital, and underdeveloped institutions. This note analyzes jobs-related projects in Uganda to identify focus areas and gaps in the portfolio in relation to country priorities mentioned in the World Bank’s country policy framework (CPF). The objective of this exercise is to understand how well the jobs agenda is being implemented through lending operations and the types of targeted jobs outcomes. This note seeks to influence future investments and analytical work in the country and provide a baseline for further analysis on jobs in the World Bank and other donors’ portfolios.